2016
DOI: 10.1016/j.jlp.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Development of a techno-economic framework for life extension decision making of safety critical installations

Abstract: One of the major decisions in management of the industrial assets is to ensure the feasibility of life extension process for safety critical components when they reach end-of-life. Most of the existing life extension decision-making models are restricted solely to either "technical" or "economic" feasibility analyses that may lead to inaccurate results or incorrect conclusions. In this paper, a comprehensive life extension feasibility assessment framewok by taking into account both the technical and economic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The RUL estimation models are either deterministic or probabilistic, but they generally incorporate degradation factors, material properties, and environmental conditions [53]. The RUL estimation models can be classified into four categories: analytical (physics-based), modelbased (data-driven), knowledge-based, and hybrid (fusion) (see Figure 2) [54][55][56][57]. The RUL methods can be further refined into a more accurate maintenance model by the use of statistical and Artificial Intelligence (AI) techniques [58].…”
Section: Other Contemporary Maintenance Strategiesmentioning
confidence: 99%
“…The RUL estimation models are either deterministic or probabilistic, but they generally incorporate degradation factors, material properties, and environmental conditions [53]. The RUL estimation models can be classified into four categories: analytical (physics-based), modelbased (data-driven), knowledge-based, and hybrid (fusion) (see Figure 2) [54][55][56][57]. The RUL methods can be further refined into a more accurate maintenance model by the use of statistical and Artificial Intelligence (AI) techniques [58].…”
Section: Other Contemporary Maintenance Strategiesmentioning
confidence: 99%
“…3) What type of integrity management programme needs to be put into place to support asset operations over the life extension period? In order to provide appropriate answers to above questions, Vaidya and Rausand (2011), Animah et al (2016) and Shafiee et al (2016) suggested, in their respective studies, that it is vital for LE decision makers to estimate the remaining useful life (RUL) of their candidate equipment, as it will enable stakeholders to achieve accurate conclusions during the LE decision-making process. Also, Liao et al (2006) suggested that when ageing degradation is detected, it is important to re-estimate the RUL in order to expedite urgent maintenance decisions and avert possible failures.…”
Section: Introductionmentioning
confidence: 99%
“…In work [6] authors consider economic and technical solutions for a possibility of prolongation of service life of safety of crucial components when they reach the termination of life term. The qualified decision about continuous work outside the service life is offered to be carried out based on estimates on two indexes: instrument assessment of technical condition and economic assessment of benefit.…”
Section: Introductionmentioning
confidence: 99%